2020
DOI: 10.1021/acssuschemeng.0c04450
|View full text |Cite
|
Sign up to set email alerts
|

Co-Oligomers of Renewable and “Inert” 2-MeTHF and Propylene Oxide for Use in Bio-Based Adhesives

Abstract: Commercial polyether polyols are usually obtained by the ring-opening polymerization of epoxides or tetrahydrofuran. 2-Methyl-tetrahydrofuran (2-MeTHF) could be an alternative bio-based building block for the synthesis of these polyols. Although 2-MeTHF cannot be polymerized, we did achieve the copolymerization of 2-MeTHF with propylene oxide (PO) using Lewis and Brønsted acids as catalysts and water or diols as initiators. The resulting polyether polyols have a molecular weight range, which allows their use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 118 publications
0
6
0
Order By: Relevance
“…All of the new polymers are amorphous and show glass-transition temperatures that get progressively lower with increasing THF selectivity ( T g = −3 to −5 °C, Figure S51). Bio-derived 2-methyl tetrahydrofuran (MeTHF), synthesized from sugars, was also investigated in reactions with PA and BO (Table , #6–8) . Using this monomer likewise resulted in successful formation of poly­(ester- alt -ethers) with up to 29% MeTHF incorporation (Figures S36–S39).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the new polymers are amorphous and show glass-transition temperatures that get progressively lower with increasing THF selectivity ( T g = −3 to −5 °C, Figure S51). Bio-derived 2-methyl tetrahydrofuran (MeTHF), synthesized from sugars, was also investigated in reactions with PA and BO (Table , #6–8) . Using this monomer likewise resulted in successful formation of poly­(ester- alt -ethers) with up to 29% MeTHF incorporation (Figures S36–S39).…”
Section: Resultsmentioning
confidence: 99%
“…Bio-derived 2-methyl tetrahydrofuran (MeTHF), synthesized from sugars, was also investigated in reactions with PA and BO (Table 2, #6−8). 54 Using this monomer likewise resulted in successful formation of poly(ester-alt-ethers) with up to 29% MeTHF incorporation (Figures S36−S39). Its NMR spectra show, in addition to the expected key assignments (no 1 H− 1 H COSY correlation between the methine-ester and methylene-ester, δ H = 5.13 and 4.35 ppm, respectively), the characteristic −CH 3 resonance from ringopened MeTHF at 1.20 ppm.…”
Section: Rocop Conditionsmentioning
confidence: 99%
“…However, in some cases, a low ring strain monomer can be incorporated into polymer chains by copolymerization with a high ring strain comonomer. 44,45 Therefore, the copolymerization of THP (low ring strain) and THF (high ring strain) was further explored. The results are shown in Table 6, which indicated that only THF was selectively polymerized (Fig.…”
Section: Inertness Of Thp To Polymerizationmentioning
confidence: 99%
“…de Vries et al realized the copolymerisation of propylene oxide with 2-MeTHF using phosphotungstic acid as the catalyst, and obtained a polyether with a relatively low molecular weight of 2 kg mol −1 . 20 Williams and co-workers investigated the terpolymerisation of phthalic anhydride with butylene oxide and 2-MeTHF. 21 They found that the copolymers contained a maximum 2-MeTHF content of 26 mol% under the condition where excessive 2-MeTHF in feed was required up to 15 times that of acid anhydride.…”
Section: Introductionmentioning
confidence: 99%